Social Security of Families in Poland – Foster Care Suport Policy - Igor POGONOWSKI; Małgorzata BŁAZEJOWSKA (Communications of International Proceedings, 2023)
Purpose: The purpose of this study is to show what forms of foster care support exist in Poland. The article attempts to classify them and assess their effectiveness. Design/Methodology/Approach: This article analyzes qualitative data on the forms of support for children placed in foster care existing in Poland. Legal acts and literature on the subject were analyzed. Findings: The results of the study show that the forms of support for families in a difficult situation functioning in Poland, although not ideal, are generally appropriate. The existing forms of support are financial or non-financial. Practical Implications: The most important practical implication is that the current support system requires constant change. Despite the positively assessed solutions, it seems reasonable to work on finding solutions that would support non-financial solutions to a greater extent.
Keywords: social security; legal security; social care; foster care